THE IMPLEMENTATION OF SUMMARIZATION STRATEGY IN TEACHING READING TO SENIOR HIGH SCHOOL - Lum'ah, Dhuriyatul (RETAIN, 2021)
This study chose reading as a subject to be studied because it was an essential skill in learning foreign language. English reading skill in senior high school had a big part to play in support the other skills in learning English. This research study was aimed to describe the implementation of the summarization strategy in teaching reading to senior high school that conducted at SMAN KABUH. This research study structured with the following questions: (1) how is the implementation of the summarization strategy in teaching reading to the tenth grade of senior high school? And (2) how are the students’ responses toward the implementation of the summarizing strategy in teaching reading?. This research study showed that the summarization strategy was helping students understand after reading a narrative text. This research also proved the benefits of summaries. The result of the observations proved that the students in grade X at SMAN Kabuh had difficulty reading skills. It was expected that teachers used a new strategy to overame the students' challenge in reading comprehension. Hence, the teacher chose the summarization strategy as suggested by the researcher. The summarization strategy was effective to help the students' problem in reading, especially about reading comprehension. The observation checklist revealed that the classroom activities were well-managed. The study's findings revealed an improvement in pupils' reading comprehension abilities. This was evident from the findings of student observations and questionnaires. All students could reach the standard. Keywords: summarizing strategy, reading, narrative text.